Reactivation of dormant "non-culturable" Mycobacterium tuberculosis developed in vitro after injection in mice: Both the dormancy depth and host genetics influence the outcome. (January 2015) - Shleeva, Margarita; Kondratieva, Tatiana; Rubakova, Elvira; Vostroknutova, Galina; Kaprelyants, Arseny; Apt, Alexander
Abstract: Three stocks of Mycobacterium tuberculosis H37Rv were cultured in vitro under prolonged hypoxic or acidified conditions until partial or complete loss of the capacity to form colonies on agar medium was achieved. Such dormant "non-culturable" mycobacteria were assessed for the growth resuscitation after intra-tracheal injection into mice of the two inbred strains with different genetic susceptibility to M. tuberculosis -triggered disease: hyper-susceptible I/St and relatively resistant B6. The results indicate that bacteria which are able to resuscitate spontaneously in liquid medium in vitro started to multiply in organs of infected mice, and that the outcome of such infection strongly depended upon the level of genetic TB susceptibility. However, dormant bacteria required inducers for resuscitation in vitro lost the capacity to multiply even in genetically susceptible mice. The established model of dormancy/reactivation is suitable for the studying host–pathogen interactions and testing vaccine and drug candidates specifically targeting latent TB. Highlights: Dormant Mycobacterium tuberculosis cells obtained in vitro lost the ability to form colonies on solid medium ("nonculturable" cells). "Nonculturable" cells were able to survive in the mammal organism (mice) and reactivate to colony forming bacteria in organs.